Perubahan Indeks Kenyang Caplak Haemaphysalis bispinosa (Acari, Ixodidae) Selama Masa Makan - Winaruddin Winaruddin (Biospecies, 2014)
The objective of this research was to know various engorgement indices and durationof attachment of female Haemaphysalis bispinosa. Two feeding experiment were designedusing the following female-male ratio 1:1 and 30:1. At same time every day up to detachmentthe body length, width and depth of females were measured using a caliper to the determine ofbody volume. Fed body weights of the females were weighed on a electric balance. The resultof this research indicates that rate of engorgement indices in females (1:1 ratio) and (30:1 ratio)increased with increasing duration of attachment (P< 0.05) and the relationship betweenduration of tick attachment was above 92%. The feeding rate of females of the 30:1 ratio waslower than that of 1:1 ratio ones up to the 72 hours in the duration attachment.